The Image Hunter - Li, Chen, 1954- (Xianggang guo ji shi ge zhi ye 2015., 2015)
This pocket-sized paperback is one of the twenty-two titles published for 2015 Hong Kong International Poetry Nights. The theme of IPHHK2015 is "Poetry and Conflict". 21 international poets from 18 different places are invited to participate in recitations, symposia and sharing sessions of the Poetry Nights. A recitation focusing on 10 local Hong Kong poets, "Hong Kong Cantonese Poetry Night" is included. This collection seeks to make accessible the best of contemporary international poetry with outstanding translations.